A content analysis of radio commentary and its adherence to the KBP code of ethics - Cataytay, Mary Grace C.; Comidoy, Merle Dawn S. (2019)
Radio commentary program has been a platform for media practitioners to freely express their opinion about different issues. However, with the prevalence of different ethical issues that media has been facing today, this research studied how radio commentary program present their content ethically to their listeners. The researcher determined if radio commentary program is still ethical amid the different assumptions and speculations to the media today. This research conducted thematic analysis that enabled the researcher to determine the overarching themes that lead to determining the common issues presented, and its tonality, approach, and manner in presenting the issues. The results show that the program most likely to argue about military, peace and order. In terms of tonality, the program tends to be more negative in presenting their arguments and issues. The radio commentators approached issues by elaborating it to its audiences. Their manner to their listeners were found out to be satirical or in a negative manner. After which, the researcher incorporates the concept of Social Responsibility theory and KBP Code of Ethics in discussing the ethical issues of the program. The researcher found out that the radio commentators violated the program standards of Kapisanan ng mga Brodkaster ng Pilipinas (KBP) Code of Ethics, which includes personal attacks; children?s program and welfare; crime and violence; sex and obscenity and pornography; and on-air language. This only implies that there is a need to review the effectiveness of the Code of Ethics towards its members of the organization (Kapisanan ng mga Brodkaster ng Pilipinas), and there is a need to penalized those radio stations who violates specific program standards, and on other media platform
Thesis (BA Communication Arts) -- University of the Philippines Mindanao, 2019